Analyzing the Use of Catholic Learning Model for the State Primary Schools in South and Southeast Pontianak - Lukas Ahen; Cenderato Cenderato; Florentina Florentina; Florentina Dwi Astuti; Arius Arifman Halawa (JETL (Journal of Education, Teaching and Learning), 2020)
Learning models were important for the teachers to apply by considering the class setting. How they could manage their class depending on what learning model they could apply. So, it was curious to know what learning model the teachers had used so far. To deal with this, the researchers were eager to find out the answer by the research. This study aims to describe the learning model, the advantages and disadvantages of using the model, and the efforts made by Catholic Education (PAK) teachers in overcoming the disadvantages and strengths of using models in the State Primary Schools in South and Southeast Pontianak. To see the use of the learning model, qualitative research methods were used which consisted of interviews, questionnaires, observations, and focus group discussions. Teachers in the State Elementary Schools in South and Southeast Pontianak had implemented the learning models: Inquiry Model, Story Telling, Role Play, and Discovery Learning contextually. Based on the result, the teacher had a strategy in the application of learning models for example: reading books that are relevant to the model to apply, inviting students to learn outside the room, taking a persuasive and personal approach. Meanwhile, some obstacles faced were the delinquency of students, less in number, a variety of competencies, the existence of students with special needs, and the lack of teaching aids. The advantages of using the learning model were systematic, involving students actively, creating cooperation, motivating students, and improving learning outcomes. The learning model tended to run monotonously. There were several efforts to overcome deficiencies of learning models: taking a personal approach, trying to maximize the use of learning models used, changing models learning that would be considered more suitable or repetitive by applying the same learning model to maximize learning outcomes, conveying material repeatedly, writing student names and adding value to students who are active in groups so they try to want to be active, giving additional assignments to students who have understood learning so students do not have to be in class and trying to maximize the tools and means of learning that exist and do to students.